ANALISIS KEKUATAN TARIK DAN IMPAK MATERIAL KOMPOSIT POLIMER DALAM APLIKASI FIBERBOAT - Rezza Ruzuqi; Victor Danny Waas (Fakultas Teknik Universitas Pattimura, 2021)
Composite material is a material that has a multi-phase system composed of reinforcing materials and matrix materials. Causes the composite materials to have advantages in various ways such as low density, high mechanical properties, performance comparable to metal, corrosion resistance, and easy to fabricate. In the marine and fisheries industry, composite materials made from fiber reinforcement, especially fiberglass, have proven to be very special and popular in boat construction because they have the advantage of being chemically inert (both applied in general and marine environments), light, strong, easy to print, and price competitiveness. Thus in this study, tensile and impact methods were used to determine the mechanical properties of fiberglass polymer composite materials. Each test is carried out on variations in the amount of fiberglass laminate CSM 300, CSM 450 and WR 600 and variations in weight percentage 99.5% -0.5%, 99% -1%, 98.5% -1, 5%, 98% -2% and 97.5%-2.5% have been used. The results showed that the greater the number of laminates, the greater the impact strength, which was 413,712 MPa, and the more the percentage of hardener, the greater the impact strength, which was 416,487 MPa. The results showed that the more laminate the tensile strength increased, which was 87.054 MPa, and the more the percentage of hardener, the lower the tensile strength, which was 73.921 MPa.